Uji Ketahanan Pisang Ambon Kuning Koleksi dari Jambi Terhadap Beberapa Vegetatif Compatibility Group (VCG) Fusarium oxysporum f. sp. cubense (Foc) - Rahmi Anna F.G; Nasril Nasir; - Jumjunidang; Catur Hermanto (Universitas Andalas, 2014)
One of prospective banana collections at Indonesian Tropical Fruits Research Institute is Ambon kuning (Gros michel) origins from Jambi. The aim of the study was to find out the response of Ambon kuning to some Vegetative Compatibility Groups (VCGs) of Fusarium oxysporum f. sp. cubense. The research was conducted from November 2012 to February 2013 in the laboratory of plant disease and the screen house of Indonesian Tropical Fruits Research Institute of Solok. The treatment used a Randomized Block Design (RBD) with 6 treatments and 4 replications, each treatment consisted of 5 plants. Treatments were 6 isolates of Foc VCGs 01213/16, 0121, 01219, 0123, 0124/5, 0120/15, those were the Indonesian Tropical Fruits Research Institutes collection. The parameters observed were percentage of plants infected, the incubation period, index of diseases severity on leaves and corm. Data was analyzed by analysis of variance. The results showed that Ambon kuning (Gros Michelcv) was resistant to Foc VCG 01219 and VCG 0120, moderately resistant to Foc VCG 0123, susceptible to Foc VCG 0121 and VCG 0124/5, and highly susceptible to Foc VCG 01213/16 Keywords: banana, resistance variety, Fusarium oxysporum f. sp. cubense, Vegetative Compatibility Group (VCG)